2023
DOI: 10.3390/gels9040274
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hydrogels for the Treatment of Bone Osteosarcoma via Localized Drug-Delivery and Tissue Regeneration: A Narrative Review

Abstract: Osteosarcoma is a malignant tumor of bone that leads to poor mortality and morbidity. Management of this cancer through conventional methods involves invasive treatment options that place patients at an increased risk of adverse events. The use of hydrogels to target osteosarcoma has shown promising results both in vitro and in vivo to eradicate tumor cells while promoting bone regeneration. The loading of hydrogels with chemotherapeutic drugs provides a route for site-specific targeted therapy for osteosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 128 publications
(190 reference statements)
0
0
0
Order By: Relevance
“…In addition to other biomaterials, hydrogels, with their biocompatibility, bioactivity, biodegradability, and osteoinductive attributes, hold promise in targeting residual tumor areas within bone defects and promoting the natural regeneration of bone at the injury site [97]. These biomimetic hydrogels closely resemble the extracellular matrix (ECM), providing vital support for the proliferation and differentiation of MSCs into osteoblasts, ultimately facilitating the restoration of lost bone tissue [97][98][99][100].…”
Section: Msc-based Strategies For Bone Regeneration In Vivomentioning
confidence: 99%
“…In addition to other biomaterials, hydrogels, with their biocompatibility, bioactivity, biodegradability, and osteoinductive attributes, hold promise in targeting residual tumor areas within bone defects and promoting the natural regeneration of bone at the injury site [97]. These biomimetic hydrogels closely resemble the extracellular matrix (ECM), providing vital support for the proliferation and differentiation of MSCs into osteoblasts, ultimately facilitating the restoration of lost bone tissue [97][98][99][100].…”
Section: Msc-based Strategies For Bone Regeneration In Vivomentioning
confidence: 99%
“…This unique characteristic enables the loading of therapeutic compounds onto the hydrogel in its liquid form, which can then be easily solidified and administered when applied. These advancements have opened doors for developing targeted hydrogels to combat osteosarcoma, aiming to induce tumor cell death and enhance survivability in patients [12]. Another study revealed a significant correlation between age and survival rate in elderly patients, demonstrating that advancing age is associated with reduced survivability.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…While data on the United States' Surveillance, Epidemiology, and End Results (SEER) program indicates a similar 5-year survival rate of 19% for lung cancer as well as 18% for liver cancer [14,15]. However, osteosarcoma is not necessarily the highest in rank for survivability among cancers of the vital organs; American kidney cancer patients have been found to experience a 5-year relative survival rate of about 75% [12]. As for comparisons against cancers of nonvital organs, osteosarcoma is often outclassed in terms of survival rates as these non-vital organs can often be removed to eliminate the cancer from the patient's body.…”
Section: -Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation